Cytotoxic and apoptotic activities in selected phyllanthaceae species of Malaysia / Sujatha a/p Ramasamy - Ramasamy, Sujatha (2012)
Phyllanthaceae species have been extensively used in folk medicine in most tropical and subtropical countries for thousand of years. However, there is a paucity of information on the cytotoxic properties of these plants. Therefore, the present study was undertaken to evaluate the cytotoxic and apoptotic activity of crude methanol (CME), hexane (CHE) and ethyl acetate (CEE) extracts of the selected Phyllanthaceae species collected from different parts of Peninsular Malaysia, namely Phyllanthus niruri (dukong anak), P. pectinatus (Pokok Melaka), P. acidus (cermai), P. roseus (Labu Kuncing), P. watsonii and Baccaurea motleyana (rambai). Cytotoxic activities were screened using an in vitro assay system of growth inhibition against four human cancer cell lines, namely breast cancer cells (MCF7), ovarian cancer cells (SKOV3), epidermal carcinoma of cervix cells (CaSki), colon cancer cells (HT29), and one normal lung fibroblast cells (MRC5). CME and CEE of P. pectinatus (leaves) exhibited potent cytotoxic activity against SKOV3 cells with IC50 values of 4.8 ± 1.04 and 5.8 ± 0.76 g/ml, respectively. CEE of P. pectinatus (fruit) exhibited strong cytotoxicity on MCF7 and CaSki cells with IC50 values of 18.1 ± 0.66 and 19.4 ± 0.53 g/ml, respectively. CHE of P. watsonii exhibited strong cytotoxicity with IC50 values of 7.9 ± 0.60, 5.8 ± 0.29, 6.9 ± 0.96 and 11.8 ± 1.61 g/ml on MCF7, SKOV3, CaSki and HT29 cells, respectively. CEE of P. watsonii demonstrated the potent cytotoxicity with an IC50 value of 3.6 ± 1.01 g/ml on CaSki cells, as well as on HT29 and SKOV3 cells with IC50 values of 5.1 ± 0.36 and 5.5 ± 0.50 g/ml, respectively. CHE of P. watsonii was further subjected for bioassay-guided fractionation and yielded 10 fractions (PW1 – PW10). PW4 – PW8 portraying a stronger cytotoxic activity against MCF7, SKOV3, CaSki and HT29 cells and was further subjected for bioassay-guided fractionation and this resulted in 8 fractions (PPW1 – PPW8). Cytotoxic activity of fraction PPW7 on MCF7, SKOV3, CaSki and HT29 cells were more active with IC50 values of 0.9 ± 0.06, 0.7 ± 0.06, 0.8 ± 0.00 and 0.8 ± 0.10 g/ml. Cytotoxic activity of CME, CHE and CEE of P. watsonii and fraction PPW7 were shown to be quite selective for cancer cells with selectivity index ranging from 4.4 to 14.6. Fraction PPW7 was subjected to LC-MS/MS analysis and six main compounds were identified. The compounds detected were ellagic acid, geranic acid, glochidone, betulin, phyllanthin and sterol glucoside. Marked morphological changes, ladder-like appearance of DNA and increment in caspase-3 activity indicating of apoptosis were clearly observed in MCF7, SKOV3, CaSki and HT29 cells-treated with cytotoxically active crude extracts of P. pectinatus (leaves and fruits), and P. watsonii, and fractions PPW6 and PPW7. It was also observed that CHE of P. watsonii arrested MCF7, SKOV3 and CaSki cells at G0/G1- S, S-G2/M and G0/G1- G2/M phases, and fraction PPW7 arrested SKOV3 cells at S and G2/M phases. Cytotoxic activity of endemic P. watsonii collected directly from Endau-Rompin Park, Johor against MCF7, SKOV3, CaSki and HT29 cells were investigated for the first time. These results demonstrated that P. watsonii has strong cytotoxic effect by inducing apoptotic cell death, increasing caspase-3 activity, and causing arrest of cancer cells at different growth phases. Hence, P. watsonii has the potential to be further exploited for the discovery and development for new anticancer pharmaceuticals.